Evaluation of incidence of cholelithiasis after bariatric surgery in subjects treated or not treated with ursodeoxycholic acid - Coupaye, Muriel; Calabrese, Daniela; Sami, Ouidad; Msika, Simon; Ledoux, Séverine (Surgery for obesity and related diseases, 2017)
The use of ursodeoxycholic acid (UDCA) to prevent gallstone formation after gastric bypass (RYGB) is still debated. Furthermore, only 1 study has assessed the effectiveness of UDCA after sleeve gastrectomy (SG) with mitigated results. To compare the incidence of cholelithiasis (CL) between patients treated or not treated with UDCA after RYGB and SG. University hospital, France. Since January 2008, a postoperative ultrasound monitoring was scheduled for all patients without previous cholecystectomy who underwent bariatric surgery in our institution. Patients who underwent at least 1 ultrasound in the first postoperative year (±6 months) were included. We started to systematically prescribe UDCA (500 mg/d) for 6 months postoperatively, in February 2012 for RYGB (once or twice daily) and in October 2013 for SG (once daily). Mean follow-up was 13.0±3.4 months. The incidence of CL was 32.5% in the 117 nontreated RYGB and 25.5% in the 51 nontreated SG. It was reduced to 2.4% in the 42 SG treated once daily (P = .005), to 5.7% in the 87 RYGB with 250 mg twice daily (P<.001), but only to 18.6% in the 102 RYGB with 500 mg once daily (P = .03). UDCA 500 mg once daily for 6 months is efficient to prevent CL 1 year after SG, but the twice-daily doses seem to be more effective after RYGB. The effectiveness of UDCA once daily after SG and the superiority of the twice-daily doses after RYGB should be confirmed with more patients and longer follow-up.